2014
DOI: 10.1128/cvi.00159-14
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and Specific Enzyme-Linked Immunosorbent Assay for Detecting Serum Antibodies against Mycobacterium avium subsp. paratuberculosis in Fallow Deer

Abstract: bThe enzyme-linked immunosorbent assay (ELISA) is the diagnostic test most commonly used in efforts to control paratuberculosis in domestic ruminants. However, commercial ELISAs have not been validated for detecting antibodies against Mycobacterium avium subsp. paratuberculosis in wild animals. In this study, we compared the sensitivities and specificities of five ELISAs using individual serum samples collected from 41 fallow deer with or without histopathological lesions consistent with paratuberculosis. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The ELISA was adapted for the diagnosis of the disease in lynx by determining the best conjugate and its optimal concentration performing a preliminary checkerboard titration using reference sera samples. The best signal-to-noise ratio of the optical densities (ODs) of the positive and negative reference sera (Prieto et al 2014) was obtained using goat anti-cat horseradish peroxidase-conjugated (SIGMA, St. Louis, USA) diluted 1500 times in blocking solution. The peroxidase substrat e employed was 3, 3′ , 5,5′tetramethylbenzidine liquid substrate (TMB) (SIGMA, St. Louis, USA).…”
Section: Elisamentioning
confidence: 99%
“…The ELISA was adapted for the diagnosis of the disease in lynx by determining the best conjugate and its optimal concentration performing a preliminary checkerboard titration using reference sera samples. The best signal-to-noise ratio of the optical densities (ODs) of the positive and negative reference sera (Prieto et al 2014) was obtained using goat anti-cat horseradish peroxidase-conjugated (SIGMA, St. Louis, USA) diluted 1500 times in blocking solution. The peroxidase substrat e employed was 3, 3′ , 5,5′tetramethylbenzidine liquid substrate (TMB) (SIGMA, St. Louis, USA).…”
Section: Elisamentioning
confidence: 99%
“…Compared to rPsoSP2-iELISA, the rPsoSP1-iELISA displayed better diagnostic e ciency with higher values of sensitivity, speci city and AUC (rPsoSP1 -rPsoSP2: 96.0% − 90.0%; 90.91% − 78.18%; 0.988 − 0.964, respectively). Although rPsoSP1 showed cross-reaction with sera from 3/10 S. scabiei-infestation, the cross-reaction between these two ectoparasites have been proved commonly in other studies [3,32,33].…”
Section: Discussionmentioning
confidence: 86%
“…Serum ELISAs for paratuberculosis detection in fallow deer ( Dama dama ) were evaluated, and their predictive values were interpreted together with the presence or absence of histologic lesions. 83 In the same study, ELISA-based results were compared pairwise to results from other testing techniques, including Ziehl–Neelsen staining, quantitative PCR, and bacterial culture. These multi-test comparisons for paratuberculosis indicated that pathogen exposure likely triggered antibody production without progressive infection.…”
Section: General Progress In Test Validation For Wild Mammal Diseasesmentioning
confidence: 99%